Analisis Produksi Biolistrik oleh Aneurinibacillus thermoaerophilus Strain N25 pada Variasi Konsentrasi Starter dalam Sistem Microbial Fuel Cell (MFC) - Echy Dania Putri; Irdawati; Azwir Anhar; Moralita Chatri (Jurnal Biogenerasi, 2026)
The increasing demand for electrical energy drives the development of renewable energy technologies such as Microbial Fuel Cell (MFC), which converts organic substrates into electricity using microorganisms. This study aims to determine the effect of starter concentration and identify the optimal concentration of Aneurinibacillus thermoaerophilus strain N25 in bioelectricity production. An experimental method was used with a dual-chamber MFC system and starter concentrations of 3%, 6%, 9%, 12%, and 15%. Voltage production was measured using a digital multimeter (V) over 24 hours. The results showed that starter concentration affected bioelectricity production, with voltage increasing over time and reaching a peak at the 20th hour. Higher starter concentrations produced higher voltage due to increased microbial activity and more efficient electron transfer.